Penggunaan Sistem Pembayaran Nirkontak untuk Mencegah Penyebaran Covid-19 di Indonesia - Kotjoprayudi, Raswyshnoe Boing; Kastaman, Kastaman (Labkat Press KA FTIK UNIKOM, 2023)
World Health Organization has classified COVID-19 as a pandemic. Many hotels were forced to close because no guests came. Scientists agree that COVID-19 cannot be stopped, experts believe it can be delayed greatly using current